Tax Morale and Conditional Cooperation - Bruno S. Frey; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2006)
Why so many people pay their taxes, although fines and audit probability are low, has become a central question in the tax compliance literature. A homo economicus, with a more refined motivation structure, helps us to shed light on this puzzle. This paper provides empirical evidence for the relevance of conditional cooperation, using survey data from 30 West and East European countries. We find a high correlation between perceived tax evasion and tax morale. The results remain robust after exploiting endogeneity and conducting several robustness tests. We also observe a strong positive correlation between institutional quality and tax morale.
Keywords: H26; H73; D64; 330; tax morale; tax compliance; tax evasion; pro-social behavior; institutions